2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33151
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Gain: Barriers and Opportunities for Integrating Sociotechnical Thinking into Diverse Engineering Courses

Abstract: Stephanie Claussen's experience spans both engineering and education research. She obtained her B.S. in Electrical Engineering from the Massachusetts Institute of Technology in 2005. Her Ph.D. work at Stanford University focused on optoelectronics, and she continues that work in her position at the Colorado School of Mines, primarily with the involvement of undergraduate researchers. In her role as an Associate Teaching Professor, she is primarily tasked with the education of undergraduate engineers. In her co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Cleopatra in FG01 said she found a sociotechnically-motivated interview assignment (see [41] for details on the assignment) valuable for emphasizing elements of real-world problem solving. She spoke of a friend who is "a civil engineer [with] a really difficult task ahead of them and they have to look at the big picture to think of a different solution when the problem seems kind of unsolvable, and it's just constant teamwork and thinking about things in different ways" (00:17:33).…”
Section: Real-world Examples In the Engineering Coursementioning
confidence: 99%
See 1 more Smart Citation
“…Cleopatra in FG01 said she found a sociotechnically-motivated interview assignment (see [41] for details on the assignment) valuable for emphasizing elements of real-world problem solving. She spoke of a friend who is "a civil engineer [with] a really difficult task ahead of them and they have to look at the big picture to think of a different solution when the problem seems kind of unsolvable, and it's just constant teamwork and thinking about things in different ways" (00:17:33).…”
Section: Real-world Examples In the Engineering Coursementioning
confidence: 99%
“…Examples during lecture and experiential examples (items that students can hold and manipulate) [31] … With in-class discussion, problem rewrites [29], interview assignment [41].…”
Section: Use Within the Classroommentioning
confidence: 99%
“…Efforts to promote sociotechnical thinking in the engineering classroom exist at different levels. Within a single course or a specific class session, educators design interventions -games, roleplaying exercises, projects -that engage students in the social dimensions of engineering problems [41], [3], [42]. These interventions often use tools like stakeholder analysis that are also common to HCD approaches.…”
Section: Sociotechnical Thinking: Contextualization For Better Engineersmentioning
confidence: 99%
“…One of their major research projects entails exploring student and faculty experiences of integrating different social justice principles in their courses. They found that students exhibit "liminal" engineering identities, meaning that their beliefs about their status as real engineers are not fully secure [15]. Moreover, they found that this liminal identity affected student beliefs about the role or importance of sociotechnical thinking in engineering.…”
Section: Sociotechnical Thinking In Engineering Educationmentioning
confidence: 99%